Dosimetric comparison of radiotherapy treatment plans done by IMRT and VMAT technique in head and neck cancer patients - Dr. Aparajeeta; Dr. Ankita Mehta; Mr. N.S. Silambarasan; Dr. Piyush Kumar (International Journal of Medical Research and Review, 2021)
Background: The increasing patient load in radiotherapy centres demands selection of the technique that provides plans with optimal dosimetry in terms of target volume coverage, organs at risk (OAR) sparing and a lesser treatment time. This study was designed to compare the two widely practised conformal techniques, IMRT and VMAT in head and neck cancer patients in terms of planning target volume (PTV) coverage, OAR sparing and treatment delivery parameters. Materials and methods: For ten postoperative head and neck cancer patients who had been treated by IMRT technique virtual VMAT plans were generated for study purposes. The dose prescribed to PTV was 60 Gy in 30 fractions. The dose-volume parameters of PTV and OARs and the treatment delivery parameters were compared amongst both the techniques. Statistical significance was calculated using paired ‘t’ test. Results: Both the plans were comparable in terms of dosimetry. The only significant difference being better conformity in the IMRT plans. The dose to OARs was also comparable in both the techniques except for a significant reduction in the point dose to brainstem with the IMRT technique. Given the treatment delivery parameters, there was a significant reduction in the treatment delivery time and monitor units with the VMAT technique compared to the IMRT technique. Conclusion: VMAT technique gave comparable plans to that of the IMRT technique in terms of dosimetry but reduced the treatment time. It seems feasible in radiotherapy centres with increased patient load.